Colour change of soft denture liners after storage in coffee and coke - Goiato, Marcelo Coelho [UNESP]; Rossatti Zuccolotti, Bruna Carolina [UNESP]; Moreno, Amalia [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP] (Wiley-Blackwell, 2011)
This study was to evaluate the colour change of soft denture liners after thermocycling and storage in coffee and coke. Four liners, two silicone-based (Sofreliner S and Reline GS) and two acrylic resin-based (Soft Confort and Dentuflex), were evaluated in this study. Ten samples were obtained for each group. After 2000 cycles of thermocycling with baths of 5 degrees C and 55 degrees C, five samples were stored in coffee and the remaining samples in coke. The colour alteration was evaluated in a reflection spectrophotometer before and after thermocycling, and after 1, 3, 24, 48 and 96 h of storage in coffee and coke. Data were submitted to anova and Tukey's HSD test (alpha = 0.05). Thermocycling and storage period represented a higher statistically significant influence for the resin liners than for the silicone materials. Coke did not influence the colour stability of the materials during storage. However, the coffee solution generated statistically significant colour alteration in the material Soft Confort. In the comparison between the coffee and coke solutions, there was no statistically significant difference for colour alteration only for the material Dentuflex. The silicone liners presented better colour stability following thermocycling and storage independent of the solution. The coffee solution was a statistically significant factor for colour alteration of the material Soft Confort.
Keywords: soft liners; resin; silicone; colour change